Moringa oleifera pods: Bibliometric analysis, properties, and food technology applications - Cauto, Alonso; Castello, Maria Luisa; Ortola, Maria Dolores (Journal of Food Technology Research, 2024)
This study examines the bibliometric analysis, properties, and food technology applications of Moringa oleifera. Moringa oleifera is a multifunctional plant with few agronomic requirements and high yields. It is well adapted to climate change, and all its parts are edible with high quality nutritional properties. There are many studies on the properties and uses of the leaves, but fewer on the pods. Consequently, the aim of this review is to carry out a bibliometric analysis that provides information regarding both the research into pods that do exist and in which areas that research is categorized, in addition to where the highest quantity of scientific groups working in the characterization of the pods may be found. This review will also highlight the primary parameters under investigation and the methods used for the analysis. From these published studies, a compilation of the compositional values (fiber, proteins, fats, amino acids, fatty acids, vitamins, minerals, and antioxidants) is shown, bearing their ripening stage in mind. Additionally, we outline the potential technological uses for the pods, aiming to improve their utilization, particularly in developed nations where this plant remains unfamiliar. Extractions of their pectin, the addition of pod powder to different foods, and their properties as low-cost adsorbents for the removal of drugs from water are some of the most remarkable uses of these pods.